بنية الحلم والواقع في الشعر الليبي المعاصر: نماذج مختارة - برهم لطفية إبراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2015)
يتخذ هذا البحث من الشعر الليبي المعاصر متناً له؛ ليشتغل على بنية الحلم والواقع، عبر محاور رئيسة هي: عتبة دخول تتناول اللغة الشعرية والذات الشاعرة، والمسافة بين الواقعي والخيالي، وبنية الحلم والواقع؛ لنجد بعد التوقف عند مجموعة من النصوص الإبداعية أن الحلم والواقع يشكلان، أو يكادان يشكلان وجهين لعملة واحدة هي النص الإبداعي؛ الذي لن يكون له حضور محقّق من دون حلم، ومن دون واقع؛ لذلك فإن امتزاج الواقع بالحلم، وتداخل هذا بذاك في النصوص الإبداعية يضفي عليها جمالية خاصة ومتعة فريدة . This research takes the Contemporary Libyan Poetry as its board, to work on the structure of the dream and reality, through major axles: threshold of entrance handling the poetic language and poetic self, and the distance between the realistic and the fantastic, and the structure of the dream and the reality, to find out after the cessation at a group of creative texts that the dream and the reality are forming, or almost forming two faces for the same coin which is the creative text, which will not have realized presence without dream, and without reality. Therefore, the mixing of reality with the dream, and the interference of this with that in the creative texts adds to it a special aesthetics and unique enjoyment.